The Happy Seeder enables direct drilling of wheat into rice stubble - Sidhu, H.S.; Manpreet-Singh; Humphreys, E.; Yadvinder-Singh; Balwinder-Singh; Dhillon, S.S.; Blackwell, J.; Bector, V.; Malkeet-Singh; Sarbjeet-Singh (Commonwealth Scientific and Industrial Research Organisation, 2007)
Lack of suitable machinery is a major constraint to direct drilling into combine-harvested rice residues due to the heavy straw load, and the presence of loose tough straw deposited by the harvester. Therefore, most rice stubbles are burnt in the mechanised rice–wheat systems of south Asia and Australia, as this is a rapid and cheap option, and allows for quick turn around between crops. As well as loss of organic matter and nutrients, rice stubble burning causes very serious and widespread air pollution in the north-west Indo-Gangetic Plains, where rice–wheat systems predominate. A novel approach with much promise is the Happy Seeder, which combines the stubble mulching and seed drilling functions in the one machine. The stubble is cut and picked up in front of the sowing tynes, which engage bare soil, and deposited behind the seed drill as mulch. Evaluation of the technology over 3 years in replicated experiments and farmers’ fields in Punjab, India, showed that establishment of wheat sown into rice residues with the Happy Seeder was comparable with establishment using conventional methods (straw burnt followed by direct drilling or cultivation before sowing) for sowings around the optimum time into stubbles up to 7.5 t/ha. For late sowings, plant density declined significantly at straw loads above 5 t/ha. The mulch also reduced weed biomass by ~60%, and reduced soil evaporation. Yield of wheat sown around the optimum time into rice residues, using the Happy Seeder, was comparable with or higher than yield after straw removal or burning, in replicated experiments and farmers’ fields, for straw loads up to 9 t/ha. In farmers’ fields there was an average yield increase of 9 and 11% in 2004–05 and 2005–06, respectively, compared with farmer practice. For sowings after the optimum time, yield declined significantly at straw loads greater than 7.5 t/ha. The Happy Seeder offers the means of drilling wheat into rice stubble without burning, eliminating air pollution and loss of nutrients and organic carbon due to burning, at the same time as maintaining or increasing yield.